Current Account Imbalances in the Southern Euro Area - Jaumotte, Florence (IMF Working Papers; Working Paper, 2010)
The paper examines the causes, consequences, and potential cures of the large current account deficits in the Southern Euro Area (SEA). These were mostly driven by a decline in private saving rates. But it was the European Monetary Union and the Euro, which enabled these countries to maintain investment rates, and thus run larger current account deficits, by improving their access to the international pool of saving. The paper finds that the deficits in SEA in 2008 were larger than can be explained by fundamentals, though the situation varies substantially across countries. It also finds that although the global financial crisis has started to force some unwinding, the current account deficits are expected to remain high in the medium run, though again with substantial variation across countries. The paper argues these large external deficits pose risks to the economy and therefore matter, even in a currency union, and discusses some policy options to reduce them.